EFFECT OF BIRTH WEIGHT ON MORTALITY AND OCCURRENCE OF DISEASES IN CROSSBRED KIDS (Indian Journal of Animal Production and Management, 2013)
Records of 2001 AB (Alpine X Beetal) and SB (Saanen x Beetal) crossbred kids upto six months of age were analyzed to study the effect of birth weight on mortality and morbidity. Irrespective of sex average birth weight was 3.06 kg. Male kids had slightly higher (3.140 ± 0.017 kg) than female (2.964 ± 0.016 kg). The mortality rate for group 1 ( 3.7 kg) were 18.20, 14.57, 14.24 and 17.71 %, respectively. In SB male kids, mortality rate was found significantly (P
Keywords: Crossbred Kids; Moriality; Birth Weight; Morbidity